INTERNATIONAL SCIENTIFIC CONFERENCE "THE SLAVIC WORLD: COMMUNITY AND VARIETY (by 1150th anniversary of the Slavic Written Language)" (Proceedings of Southern Federal University. Philology, 2013)
Flyagina M.V.Keywords: culture, linguistics, Slavic writing language.This article focuses on the International Scientific conference «The Slavic world: similarity and diversity» dedicated to the celebration of the Day of Slavic writing system and culture. Special attention was paid to the problems of Saints Cyril and Methodius life and work, the development of Slavic Literature in Europe during the early Middle Ages, the issues of corpus-based Slavic writing system. The diversity of reports and high level of the conference point out that modern Slavonic studies is of high potential for further research.